Pelatihan Budidaya Tanaman secara Hidroponik kepada Tenaga Penyuluh dan Kelompok Tani Kecamatan Bumi Makmur, Kabupaten Tanah Laut: Hydroponic Plant Cultivation Training for Extension Workers and Farmer Groups in Bumi Makmur District, Tanah Laut Regency - Jawak, Gani; Ismuhajaroh, Bakti Nur; Rusmayadi, Gusti; Juharni, Juharni; Wahdah, Raihani; Langai, Bambang Fredrickus; Fadhiel, Muhammad Ihsan; Rambe, Mikhael Wesley; Nababan, Endang Mayjela Enjelika; Yakub, Yakub (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Bumi Makmur District is located in a swampy area with the main livelihood being rice cultivation. Vegetables cannot be produced in this region because the swamp soil is acidic and pyrite. One of the solutions offered to meet the needs of vegetables is hydroponic cultivation. Hydroponic training was carried out to increase public knowledge about the cultivation of vegetable crops with hydroponics by socialization and practice of wick system hydroponics. The training participants were Field Agricultural Extension Workers and Farmer Groups, carried out in the hall of the Bumi Makmur Agricultural Extension Center. The number of training participants was 24 people, consisting of 20 men and 4 women. All of the training participants were >18 years old with education levels ranging from junior high school to Master's level. The trainees who had heard the term hydroponics through the internet, radio/television, print media, family, and school were 91.67%. Participants who had cultivated vegetable crops with hydroponics were only 4.17% and planned to cultivate plants hydroponically was 83.33%. A total of 93.83% of participants had never and 95.83% were interested in participating in hydroponic training. The final survey showed that 95.83% of participants wanted to take part in advanced training on hydroponic systems and techniques with hands-on practice methods and a training duration of 2-3 days. Only 58.33% of participants rated hydroponic training as very important. The results of the basic ability test about the participants' knowledge of hydroponics showed an increase in the average score from the initial 50.00 to 68.7.